Multilocus, DNA-based phylogenetic analyses reveal three new species lineages in the Phellinus gabonensis–P. caribaeo-quercicola species complex, including P. amazonicus sp. nov. (1st September 2016) - de Campos-Santana, Marisa; Amalfi, Mario; Castillo, Gabriel; Decock, Cony
Abstract : Species complexes in the poroid Hymenochaetaceae are well documented in the temperate areas. Potential species complexes are less known in tropical areas, however. In the last ten years, four phylogenetically and morphologically closely related species of Phellinus (Hymenochaetaceae) were described from various tropical/subtropical areas viz. P. caribaeo-quercicola, P. gabonensis, P. ellipsoideus, and P. castanopsidis . They are characterized by cushion-shaped basidiomata, ventricose, commonly hamate hymenial setae, and broadly ellipsoid, thick-walled, pale yellowish basidiospores. Pursuing the studies of this complex, a phylogenetic approach based on DNA sequence data from the nuc rDNA regions ITS1-5.8S-ITS2 (ITS) and partial 28S (including the domains D1, D2, D3) and on part of the translation elongation factor 1-α ( tef1, region between exons 4 and 8) revealed three new lineages or phylogenetic species. Two of these phylogenetic species are composed of exclusively on Neotropical specimens. One of them, described below as Phellinus amazonicus sp. nov., is represented by multiple collections originating from Neotropical, lowland, dense, moist forest at the western edge of the Amazon Basin in Ecuador, the Guiana Shield in French Guiana and (more likely) Trinidad. The second Neotropical phylogenetic species is represented in our phylogenetic analyses by a single collection from northeastern Argentina. It is also potentially known from two herbarium specimens originating from southern Brazil, for which no sequence data is available. It is left for now as Phellinus sp. 1, waiting to gather more specimens and DNA sequences data. The third new phylogenetic species is known by a single collection (pure culture) of uncertain origin. It is thought to represent Phellinus setulosus, a Southeast Asian taxa. From an evolutionary perspective, tree species occurring in the Neotropics ( P. amazonicus, P. caribaeo-quercicola, and Phellinus sp. 1) have a closely related genetic background and form a well supported Neotropical lineage.